The Effect of Plant Density and Duration of Irrigation in Yield and Yield Content of ( Zea mays L. )/تأثير مسافات الزراعة بين النباتات ومدد الري في الحاصل ومكوناته لمحصول الذرة الصفراء ( Zea mays L. ) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2017)
A field experiment was conducted at center of guiding agricultural Al – Muhanawial / Babil , during the Fall season 2014 . using split plot design arrangement according to randomized block design with three replication was used to study the effect of density among plants (15,25, 35) cm and duration of irrigation (irrigation every five and Ten days ) in  the yield and it's components of maize. The results showed  that significant differences among plant density and duration of irrigation and the interaction for the study traits except the number of ears and 500 grain weight. The densitly (35.cm ) was superior by giving high value for the following traits : number of ears/plant, number of rows/ear , number of grains/row and grains yield: ( 1.268, 17.01, 39.22, 208.37) Sequencey , it supered on the effect of other density (15.25cm) were gave the value:[(1.125,1.203), (15.26, 16.62), (34.78 , 38.58 ) and (171, 87) 197.22)] sequencey . While the duration irrigation were superior ( irrigation every 5 day ) by giving high value : 1.260, 16.70, 38.72,146.15 and 221.11) for the traits: number of ears/plant , number of rows / ear, number of grains/row , grain 500 weight and grain yield Sequencey .when the introduction between them was significnat at the traits : number of rows / ear, number of grains / row and grains yield : the interaction (15 cm density x irrigation every 5 days ) was superior by giving high value (17.29 , 40.50 , and 237.11) for the tralts : number of rows/ear , number of grains / row and grains yield sequencey . But the interaction was not significant at the number of ear / plant and grain 500 weight .